2018
DOI: 10.1515/jpm-2017-0127
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental outcome at the age of 4 years according to the planned mode of delivery in term breech presentation: a nationwide, population-based record linkage study

Abstract: The absolute risk of abnormal neurological outcome in breech deliveries at term was low, regardless of planned mode of birth. Planned vaginal breech labor did not increase the risk for abnormal neurological outcome compared to planned cesarean section.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…This is most likely due to the association of vaginal breech delivery with an increased risk of short-term neonatal morbidity [3][4][5]. Many obstetricians and women choose a cesarean section as the mode of delivery to avoid these possible complications, even if the long-term neurological outcome of the infants is normal when mothers and fetuses are well selected, and the deliveries are handled with caution [6,7]. This decision might seem controversial, as a cesarean section might cause adverse long-term health problems in the offspring, and the uterus scar created by the cesarean section increases the complication risks for the mother during subsequent pregnancies and deliveries [1,[8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…This is most likely due to the association of vaginal breech delivery with an increased risk of short-term neonatal morbidity [3][4][5]. Many obstetricians and women choose a cesarean section as the mode of delivery to avoid these possible complications, even if the long-term neurological outcome of the infants is normal when mothers and fetuses are well selected, and the deliveries are handled with caution [6,7]. This decision might seem controversial, as a cesarean section might cause adverse long-term health problems in the offspring, and the uterus scar created by the cesarean section increases the complication risks for the mother during subsequent pregnancies and deliveries [1,[8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Ulander et al report no difference in long-term outcomes between breech and cephalic babies born vaginally [39]. Two studies, including the TBT, compared the long-term outcomes of breech presentations born vaginally or by C-section and found no differences [10,40]. In Europe, the Nordic countries also promote vaginal breech delivery however we found no reports of breech clinics in these regions.…”
Section: Discussionmentioning
confidence: 56%
“…Ulander et al report no difference in long-term outcomes between breech and cephalic babies born vaginally [ 39 ]. Two studies, including the TBT, compared the long-term outcomes of breech presentations born vaginally or by C-section and found no differences [ 10 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…46 studies (73%) employed methods to enhance quality of measures by suitable training, repetition, or adjusting for confounding factors. 3 studies reported composite outcomes studying childhood adverse neurodevelopmental outcome, neonatal morbidity outcomes, and maternal and neonatal complications (Appendix S3) [20][21][22] .…”
Section: Resultsmentioning
confidence: 99%